The Effect of Inflation Rate, Interest Rate and Rupiah Exchange Rate on Value Added Tax (VAT) Revenue at KPP Pratama Cirebon 1 Period 2021-2024 - Galih Randiyanto, Rama; Kurnia Syaharani, Fitri; Anand, Dev (DINASTI RESEARCH, 2025)
This study analyzes the impact of inflation, interest rates, and the rupiah exchange rate on value-added tax (VAT) revenue. VAT is a tax levied on the consumption of goods and services within customs territories. The research population encompasses monthly data from 2021 to 2024, comprising inflation rates in West Java, Bank Indonesia's benchmark interest rates, the exchange rate of the rupiah against the US dollar (USD), and VAT revenue at the KPP Pratama Cirebon I. The data analysis techniques employed in this study encompass descriptive statistical analysis, classical assumption tests, and the coefficient of determination. The results indicate that there is a significant negative relationship between inflation and VAT revenue. In contrast, the benchmark interest rate and the exchange rate of the rupiah do not exert a substantial influence on VAT revenue.